The Precision of Calculating the Optical Power of the IOL in Various Methods of Out-Bag IOL Fixation - Yu. N. Yusef; A. S. Vvedenskiy; M. N. Ivanov; L. Alkharki; N. D. Fokina (Oftalʹmologiâ)
The calculation of the optical power of the IOl for out-bag implantation remains one of the actual problems of cataract surgery. Purpose. Comparative study of the precision of calculating the optical power of the IOL for retropupillary fixation of an iris-claw lens, transscleral fixation of a rigid IOL with two flexible haptic elements and transscleral fixation of an soft hydrophobic IOL with two open haptic elements. Patients and methods. The study included 105 patients (108 eyes) with complicated phacoemulsification in combination with lens subluxation. First group included 39 patients (42 eyes) with complicated phacoemulsification and retropupillary implantation of an iris-claw lens. Second group included 29 patients (29 eyes) with complicated phacoemulsification and transscleral suture fixation of rigid PMMA IOL. Third group included 37 patients (37 eyes) with complicated phacoemulsification and transscleral suture fixation of an soft hydrophobic IOL with two open haptic elements. In the postoperative period we performed a comparative evaluation of visual acuity without correction and best corrected visual acuity, IOL optical power calculation precision within ±0.5 diopters, the average absolute error of IOL optical power calculation. Results. Three months after the operation the visual acuity of 0.8–1.0 without correction was obtained in 35,7 % of cases in the 1st group, 17.2 % in the 2nd group, 16.2 % in the 3rd group. The precision of postoperative refraction within ±0.5 diopters was 95.2 % in the 1st group, 86.2 % in the 2nd group 83.7 % in the 3rd group. The average absolute error of IOL optical power calculation was 0.33 ± 0.07 diopters in the 1st group, 0.57 ± 0.18 diopters in the 2nd group, 0.62 ± 0.19 diopters in the 3rd group (р < 0.05). Three months after surgery there were no significant differences in best corrected visual acuity and the degree of induced astigmatism. Conclusion. Retropupillary implantation of an iris-claw lens during complicated phacoemulsification significantly increases visual acuity without correction, frequency calculation precision within ±0.5 diopters, significantly reduces the average absolute calculation error compared to transscleral suture fixation of the IOL.